2014
DOI: 10.3390/ijerph110303185
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact Assessment and End-of-Life Treatment Policy Analysis for Li-Ion Batteries and Ni-MH Batteries

Abstract: Based on Life Cycle Assessment (LCA) and Eco-indicator 99 method, a LCA model was applied to conduct environmental impact and end-of-life treatment policy analysis for secondary batteries. This model evaluated the cycle, recycle and waste treatment stages of secondary batteries. Nickel-Metal Hydride (Ni-MH) batteries and Lithium ion (Li-ion) batteries were chosen as the typical secondary batteries in this study. Through this research, the following results were found: (1) A basic number of cycles should be def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…The error bars indicate the intervals (with 2.5-97.5% probability) which include all the potential results achieved under the uncertainty analysis. This result is in agreement with Yu et al' study [13], in which a close dependence between recycle rate and life cycle environmental impacts of a Li-ion battery was reported. In a study by Zackrisson et al [9], a low amount of environmental impacts was reported for the end-of-life treatment phase and they considered transport to recycling as the main factor in this phase which is responsible for the lowest global warming impacts through the whole battery life cycle.…”
Section: Uncertainty Analysissupporting
confidence: 93%
See 3 more Smart Citations
“…The error bars indicate the intervals (with 2.5-97.5% probability) which include all the potential results achieved under the uncertainty analysis. This result is in agreement with Yu et al' study [13], in which a close dependence between recycle rate and life cycle environmental impacts of a Li-ion battery was reported. In a study by Zackrisson et al [9], a low amount of environmental impacts was reported for the end-of-life treatment phase and they considered transport to recycling as the main factor in this phase which is responsible for the lowest global warming impacts through the whole battery life cycle.…”
Section: Uncertainty Analysissupporting
confidence: 93%
“…This result is in agreement with Yu et al .' study , in which a close dependence between recycle rate and life cycle environmental impacts of a Li‐ion battery was reported. In a study by Zackrisson et al .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Crude recycling and disposal practices of electronic waste (e-waste; such as LIBs) often result in the production of toxic substances (e.g., dioxins) and the leaching of toxic heavy metals into the environment [3][4][5]. Currently, there are only a few commercial operations capable of recovering metals from LIB waste, largely located in Asia and Europe [6].…”
Section: Introductionmentioning
confidence: 99%